A COMPARATIVE STUDY OF "LIGHT" AND "QING" IN ENGLISH AND CHINESE: A LEXICAL SEMANTIC MAPPING APPROACH - A, François (Economics and Statistics Research Journal (ESRJ), 2022)
This study explores the semantic meanings of the Chinese word “qing” and its English counterpart “light” through the lens of Lexical Typology, with a focus on polysemy - the phenomenon of words having multiple meanings. Utilizing François' (2008) framework, the study analyzes the functional properties and empirical observations of “light” and compares them with “qing” to identify similarities and differences between these two languages. The research methods include sense classification, connecting senses, and lexical semantic mapping. An etic grid for the semantic study of “light” and an emic categorization of “qing” and “light” are provided. The study demonstrates that polysemy facilitates efficient and expressive communication, enabling people to convey complex objective phenomena. By utilizing the Lexical Typology framework, the study highlights the fine distinctions between different senses of the same word and reveals the co-lexicalization that comes from individual words, which is crucial for cross-linguistic comparison. To facilitate comparative research, the study emphasizes the need for explicit skills in different languages